Concept Evaluation of Radical Short–Medium-Range Aircraft with Turbo-Electric Propulsion - Vankan, W.J.; Lammen, W.F.; Scheers, E.; Dewitte, P.A.R.; Defoort, S. (MDPI, 2024)
Ambitious targets for the coming decades have been set for further reductions in aviation greenhouse gas emissions. Hybrid electric propulsion (HEP) concepts offer potential for the mitigation of these aviation emissions. To investigate this potential in an adequate level of detail, the European research project IMOTHEP (Investigation and Maturation of Technologies for Hybrid Electric Propulsion) explores key technologies for HEP in close relation with developments of aircraft missions and configuration. This paper presents conceptual-level design investigations on radical HEP aircraft configurations for short–medium-range (SMR) missions. In particular, a blended-wing-body (BWB) configuration with a turbo-electric powertrain and distributed electric propulsion is investigated using NLR’s aircraft evaluation tool MASS. For the aircraft and powertrain design, representative top-level aircraft requirements have been defined in IMOTHEP, and the reference aircraft for the assessment of potential benefits is based on the Airbus A320neo aircraft. The models and data developed in IMOTHEP and presented in this paper show that the turbo-electric BWB configuration has potential for reduced fuel consumption in comparison to the reference aircraft. But in comparison to advanced turbofan-powered BWB configurations, which have the same benefits of the BWB airframe and advanced technology assumptions, this potential is limited. Keywords: hybrid electric propulsion; HEP; turbo-electric; blended-wing-body; energy efficiency